Tutorial: Multiplying and factoring algebraic expressions
This tutorial: Part A: Multiplying algebraic expressions
Single step calculations
One of the most important mathematical tools for multiplying algebraic expressions is the distributive law for real numbers:
#[Distributive law for real numbers][Ley distributiva para los números reales]#
#[If $a,$ $b,$ and $c$ are any real numbers, then:][Si $a, b,$ y $c$ son cualquieras números reales, entonces:]#
Suggested video for this topic: Video by Papapodcasts
#[Law][Ley]# | Examples |
$a(b \pm c) = ab \pm ac$
#[Left distributive law][Ley distributiva izquierda]# |
$x(x+1)$\t = $x(x) + x(1) $ \\ \t ${}=x^2 + x$
$x^3(y-x)$\t ${}= x^3(y) - x^3(x) $ \\ \t ${}=x^3y - x^4$
$-7(x+y+z)$
${}= (-7)x + (-7)y + (-7)z$ *
${}=-7x - 7y - 7z$ $\dfrac{4x^2}{3y}\left(\dfrac{xy^2}{2z} - \dfrac{y}{x}\right)$
${}= \dfrac{4x^2}{3y}\left(\dfrac{xy^2}{2z}\right) - \dfrac{4x^2}{3y}\left(\dfrac{y}{x}\right)$
${}= \dfrac{4x^2\cdot xy^2}{3y\cdot 2z} - \dfrac{4x^2\cdot y}{3y\cdot x}$
#[Rule for multiplying fractions][Relga para multiplicar fracciones]#
${}= \dfrac{4x^3y^2}{6yz} - \dfrac{4x^2y}{3xy}$
#[Rules for exponents][Relgas para exponentes]#
${}= \dfrac{2x^3y}{3z} - \dfrac{4x}{3}$
|
$(a \pm b)c = ac \pm bc$
#[Right distributive law][Ley distributiva derecha]# |
$(x+1)y$\t ${}=x(y) + 1(y) $ \\ \t ${}=xy + y$
$(1-3x+x^2)x$
${}=1(x) - 3x(x) + x^2(x)$
${}=x - 3x^2 + x^3$ $\left(\dfrac{xy^2}{2z} + \dfrac{2y}{3x}\right)\dfrac{z}{xy^2}$
${}= \dfrac{xy^2}{2z}\left(\dfrac{z}{xy^2}\right) + \dfrac{2y}{3x}\left(\dfrac{z}{xy^2}\right)$
${}= \dfrac{xy^2\cdot z}{2z\cdot xy^2} + \dfrac{2y\cdot z}{3x\cdot xy^2}$
#[Rule for multiplying fractions][Relga para multiplicar fracciones]#
${}= \dfrac{xy^2z}{2xy^2z} + \dfrac{2yz}{3x^2y^2}$
#[Rules for exponents][Relgas para exponentes]#
${}= \dfrac{1}{2} + \dfrac{2z}{3x^2y}$
|
* #[We can justify the use of the distributive law with three (or more) summands in the parentheses by arguing as follows:][
Podemos justificar el uso de la ley distributiva con tres (o más) sumandos en los paréntesis como sigue:]#
$a(b+c+d)$ \t ${}= a(b+[c+d])\quad$ \t #[Think of $b+c+d$ as ][Piensa en $b+c+d$ como]# $b+[c+d].$
\\ \t ${}= ab+a[c+d]$ \t #[Distributive law for two summands][Ley distributiva para tres sumandos]#
\\ \t ${}= ab+ac+ac$ \t #[Distributive law for two summands again][Ley distributiva para tres sumandos otra vez]#
Multi-step calculations
If what we are distributing is itself a sum or difference, then it is necessary to apply the distributive law more than once:
Examples
$\color{crimson}{(2x+1)}(3x-2)$ \t ${}=\color{crimson}{(2x+1)}(3x)\ \ + \ \ \color{crimson}{(2x+1)}(-2)$ \gap[40] \t #[Distribute the ][Distribuya la]# $\color{crimson}{(2x+1)}$
\\ \t ${}=6x^2 + 3x \ \ - \ 4x - 2$ \t #[Apply the distributive law to each summand.][Aplica la ley distributiva a cada sumando.]#
\\ \t ${}=6x^2 - x - 2$ \t #[Simplify (combine the $3x$ and $-4x$).][Simplifica (combina la $3x$ y la $-4x$).]#
\\
\\ $\color{crimson}{(1 - y)}(1 + y - y^2)$ \t ${}=\color{crimson}{(1 - y)}(1)\ \ + \ \ \color{crimson}{(1 - y)}(y)\ \ - \ \ \color{crimson}{(1 - y)}(y^2)$ \t #[Distribute the ][Distribuya la]# $\color{crimson}{(1 - y)}$
\\ \t ${}=1 - y\ \ + \ \ y - y^2\ \ - \ \ (y^2 - y)$ \t #[Apply the distributive law to each summand.][Aplica la ley distributiva a cada sumando.]#
\\ \t ${}=1 - y \ \ + \ \ y - y^2\ \ - \ \ y^2 + y$ \t #[Distribute the minus sign.][Distribuya el signo menos.]#
\\ \t ${}=1 + y - 2y^2$ \t #[Simplify.][Simplifica.]#
FOIL Method
There is quicker way of expanding expressions such as the first and second one above, called the "FOIL" method.
%%FOIL
The FOIL method is used to expand products of the form
$(a + b)(c + d)$
#[as follows:][como sigue:]#
\\ \t #[F][P]# \t #[First][Primeros]# \t #[Multiply the first terms.][Multiplica los términos primeros]# \t $\color{#aaaaaa}{(\bold{\color{#c1026f}{a}} + b)(\bold{\color{#c1026f}{c}} + d)}$ \t $\color{#c1026f}{a \times c = ac}$
\\ \t #[O][EX]# \t #[Outer][EXternos]# \t #[Multiply the outer terms.][Multiplica los términos externos]# \t $\color{#aaaaaa}{(\bold{\color{#0ea05e}{a}} + b)(c + \bold{\color{#0ea05e}{d}})}$ \t $\color{#0ea05e}{a \times d = ad}$
\\ \t #[I][IN]# \t #[Inner][INternos]# \t #[Multiply the inner terms.][Multiplica los términos internos]# \t $\color{#aaaaaa}{(a + \bold{\color{#026fc1}{b}})(\bold{\color{#026fc1}{c}} + d)}$ \t $\color{#026fc1}{b \times c = bc}$
\\ \t #[L][UL]# \t #[Last][ÚLtimos]# \t #[Multiply the last terms.][Multiplica los términos últimos]# \t $\color{#aaaaaa}{(a + \bold{\color{#de6c00}{b}})(c + \bold{\color{#de6c00}{d}})}$ \t $\color{#de6c00}{b \times d = bd}$
Then add them all up
#[Result][Resultado]# \gap[10] \t $(a+b)(c+d) = \color{#c1026f}{ac} + \color{#0ea05e}{ad} + \color{#026fc1}{bc} + \color{#de6c00}{bd}$ \t #[F][P]# #[O][EX]# #[I][IN]# #[L][UL]#
Suggested video for this topic: Video by MATHRoberg
Examples
$(x + 1)(3x - 2)$ \t ${}=\color{#c1026f}{x \cdot (3x)} + \color{#0ea05e}{x \cdot (-2)} + \color{#026fc1}{1 \cdot (3x)} + \color{#de6c00}{1 \cdot (-2)}$ \t \gap[20] FOIL \\ \t ${}=3x^2 -2x + 3x -2$
\\ \t ${}=3x^2 +x -2$
\\ \t
\\ $(x - 3)(x + 3)$ \t ${}=\color{#c1026f}{x \cdot (x)} + \color{#0ea05e}{x \cdot 3} + \color{#026fc1}{(-3) \cdot x} + \color{#de6c00}{(-3) \cdot 3}$ \t \gap[20] FOIL \\ \t ${}=x^2 + 3x - 3x - 9$
\\ \t ${}=x^2 - 9$
Special cases
The second example above, and some you filled in, are important enough to warrant special mention.
#[Some identities][Algunas identidades]#
#[If $a$ and $b$ are any real numbers, then:][Si $a$ y $b$ son cualquieras números reales, entonces:]#
Suggested video for this topic: Video by Math and Science
#[Identity][Identidad]# | Examples |
#[Difference of two squares][Diferencia de dos cuadrados]#:
$(a + b)(a - b)$ \t ${}=a^2-b^2$ \\ $(a - b)(a + b)$ \t ${}=a^2-b^2$
(#[See the second example of %%FOIL above.][Ve el segundo ejemplo de %%FOIL de arriba.]#)
|
$(x-3)(x+3)$ \t ${}=x^2 - 3^2$ \\ \t ${}= x^2 - 9$
$(3x + 4y)(3x - 4y)$ \t ${}=(3x)^2 - (4y)^2$ \\ \t ${}=9x^2 - 16y^2$
|
#[Square of a sum or difference][Cuadrado de una suma o diferencia]#:
$(a + b)^2$ \t ${}=a^2 + 2ab + b^2$ \\ $(a - b)^2$ \t ${}=a^2 - 2ab + b^2$
(#[See the second question above.][Ve la segunda pregunta de arriba.]#)
|
$(x + 3)^2$ \t ${}=x^2 + 2(x)(3) + 3^2$ \\ \t ${}=x^2 + 6x + 9$
\\ $(3x + 4y)^2$ \t ${}= (3x)^2 + 2(3x)(4y) + (4y)^2$ \\ \t ${}= 9x^2 + 24xy + 16y^2$
\\ $(3x - 4y)^2$ \t ${}=(3x)^2 - 2(3x)(4y) + (4y)^2$ \\ \t ${}=9x^2 - 24xy + 16y^2$
|
Now try the exercises in Section 0.4 in Finite Mathematics and Applied Calculus.
or move ahead to the next tutorial by pressing "Next tutorial" on the sidebar.
Copyright © 2021 Stefan Waner and Steven R. Costenoble